Capital structure, working capital management and potential growth of a business: the case of the Sri Lankan stockbroking industry / Chamil Wansaja Senarathne and Viraj Malawana. - Senarathne, Chamil Wansaja; Malawana, Viraj (Accounting Research Institute and UiTM Press, 2019)
The objective of this paper is to examine the financial and strategic implications of regulatory restrictions for working capital management of firms operating in the stockbroking industry. The present regulatory frameworks require banks and other financial services sector firms to have more equity capital in the capital base, without regard to the financial and operating characteristics of the firms. Based on the Sri Lankan stockbroking industry, this paper shows how the return on equity deteriorates and potential growth restricted, when the regulations require firms to deduct certain assets from the capital base to meet the minimum capital requirements. The results show that the potential growth and return on equity reduce substantially after compliance with the regulation. Further, the regulation restricts a firm's attempt to diversify the collateral portfolio in the market in order to reduce the systematic risk attached to the securities in the collateral portfolio. These regulatory restrictions also add an additional stress level to corporate management to leverage the number of times of sales (sales turnover) in order to overcome the issue, which may result in overtrading. It may also create ethical issues on soliciting clients and induce them to trade in the stock market, without proper justifications.